The role of inflammation in silicosis - Liu, Tong-Tong; Sun, Hai-Fei; Han, Yan-Xing; Zhan, Yun; Jiang, Jian-Dong (Frontiers in Pharmacology, 2024)
Silicosis is a chronic illness marked by diffuse fibrosis in lung tissue resulting from continuous exposure to SiO2-rich dust in the workplace. The onset and progression of silicosis is a complicated and poorly understood pathological process involving numerous cells and molecules. However, silicosis poses a severe threat to public health in developing countries, where it is the most prevalent occupational disease. There is convincing evidence supporting that innate and adaptive immune cells, as well as their cytokines, play a significant role in the development of silicosis. In this review, we describe the roles of immune cells and cytokines in silicosis, and summarize current knowledge on several important inflammatory signaling pathways associated with the disease, aiming to provide novel targets and strategies for the treatment of silicosisrelated inflammation.